Reduction of Ochratoxin A during the Preparation of Porridge with Sodium Bicarbonate and Fructose - Hyun Jung Lee; Shufang Li; Kejia Gu; Dojin Ryu (Toxins, 2021)
Ochratoxin A (OTA) is a potential human carcinogen that poses a significant concern in food safety and public health. OTA has been found in a wide variety of agricultural commodities, including cereal grains. This study investigated the reduction of OTA during the preparation of rice- and oat-based porridge by a simulated indirect steam process. The effects of sodium bicarbonate (NaHCO3) and fructose on the reduction of OTA were also investigated. During the processing, OTA in rice- and oat-porridge was decreased by 59% and 14%, respectively, from initial OTA artificially added at 20 μg/kg (dry weight basis). When 0.5% and 1% of sodium bicarbonate were added to rice porridge, increased reduction of OTA was observed as 78% and 68%, respectively. The same amounts of added sodium bicarbonate also further reduced OTA in oat porridge to 58% and 72%, respectively. In addition, increased reduction of OTA in the presence of fructose was observed. A combination of the two, i.e., 0.5% sodium bicarbonate and 0.5% fructose, resulted in a 79% and 67% reduction in rice porridge and oat porridge, respectively. These results indicate that indirect steaming may effectively reduce OTA in preparation of porridge-type products, particularly when sodium bicarbonate and/or fructose are added.